DMD genotypes and loss of ambulation in the CINRG Duchenne Natural History Study. (26th July 2016) - Bello, Luca; Morgenroth, Lauren P.; Gordish-Dressman, Heather; Hoffman, Eric P.; McDonald, Craig M.; Cirak, Sebahattin
Abstract : Objective: To correlate time to loss of ambulation (LoA) and different truncating DMD gene mutations in a large, prospective natural history study of Duchenne muscular dystrophy (DMD), with particular attention to mutations amenable to emerging molecular treatments. Methods: We analyzed data from the Cooperative International Neuromuscular Research Group Duchenne Natural History Study for participants with DMD single- or multi-exon deletions or duplications with defined exon boundaries (n = 186), or small mutations identified by sequencing (n = 26, including 16 nonsense point mutations). We performed a time-to-event analysis of LoA, a strong indicator of overall disease severity, adjusting for glucocorticoid treatment and genetic modifiers. Results: Participants with deletions amenable to skipping of exon 44 had later LoA (median 14.8 years, hazard ratio 0.31, 95% confidence interval 0.14–0.69, p = 0.004). Age at LoA did not differ significantly in participants with deletions amenable to exon 45, 51, and 53 skipping, duplications, and small rearrangements. Nonsense mutation DMD also showed a typical median age at LoA (11.1 years), with a few outliers (ambulatory around or after 16 years of age) carrying stop codons within in-frame exons, more often situated in the rod domain. Conclusions: As exon 44 skipping–amenable DMD has a later LoA, mutation-specific randomization and selection of placebo groups are essential for the success of clinical trials.